Purchasing-power flows in retailing: A forecasting model based on gravitation theory - Suntum, Ulrich van (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This article presents a model based on gravitation theory to anticipate inter-regional purchasing-power flows in the retail sector, and demonstrates how this model may be applied empirically by considering the example provided by the county of Mettmann. Unlike previous forecasting models, this model makes it possible to dispense with setting an arbitrary maximum size for catchment areas. It also enables all of the bilateral purchasing-power flows between a large number of towns or regions, and the key factors influencing them, to be investigated simultaneously. The empirical findings for the county of Mettmann appear extremely plausible. The author discusses three possible areas of application for this forecasting model: to gauge the effectiveness of city-marketing measures; to assess the effects of large (e.g. out-of-town) retail centres; and to predict the impacts of improvements to the road network on retailing in both source and target localities. The results produced by the model are in some cases surprising; the model is, however, capable of providing good explanations for these surprises.